Novel approaches to pancreas allograft surveillance - Barnes, J (2019)
Pancreas transplantation is a successful treatment option for selected patients with advanced complications of diabetes. It offers insulin independence, stabilisation of diabetic complications, and improved survival. However, these are largely conditional on long term pancreas allograft survival. Pancreas graft survival is poorer than that of other transplanted organs and this is mainly due to the absence of accurate and reliable techniques for monitoring the pancreas allograft. Irreversible damage has usually occurred to the pancreas before rejection is diagnosed, such that treatment which would otherwise have been effective, brings no benefit.